Family Well-being in the Digital Age: A Systematic Review of Social Media Literacy using ADO and TCM Framework - Putri, Aisyah Puspita; Herawati, Tin; Simanjuntak, Megawati (Faculty of Psychology Universitas Gadjah Mada, 2025)
Social media platforms are now inseparable from children as well as parents, making social media literacy a critical skill for maintaining family well-being in the digital age. This analysis explores whether social media literacy genuinely influences family well-being, as reflected in how each family member engages with social media. A systematic literature review was conducted using Antecedents, Decisions, Outcomes (ADO) and Theory, Context, Method (TCM) frameworks analyzing 66 studies. Findings identified five main antecedents: individual and psychological factors, social and family influences, access to media and technology, intervention and empowerment, and cultural and environmental context. These antecedents shape family decisions: responsible digital use, parental mediation, privacy, and the use of social media for education and advocacy, impacting the objective and subjective well-being of the family both positively and negatively. The review highlights theoretical, contextual and methodological gaps including geographical bias towards Western countries, the dominance of cross-sectional studies and limited focus on intergenerational digital literacy.